Dynamic pedobarography transitional objects by Lagrange's equation with FEM, modal matching and optimization techniques - Raquel Ramos Pinho (2004)
This paper presents a physics-based approach to obtain 2D or 3D dynamic pe-dobarography transitional objects from two given images (2D or 3D). With the used methodology, we match nodes of the input objects by using modal matching, improved with optimization techniques, and solve the Lagrangian dynamic equilibrium equation to obtain the intermediate shapes. The strain energy involved can also be analysed and used to quantify local or global deformations.